Parents' Perceptions about the Mobile Technology Use of Preschool Aged Children - Genc, Zulfu (Elsevier Science Bv, 2014)
In the modern media world-22 years after the birth of the World Wide Web, 15 years after the launch of Google, 10 years after the first social networking site, eight years after the first YouTube video, six years after the first touch-screen smartphone, five years after the first app store, and two years after the iPad children grow up alongside technology that changes at lightning speed. At only a few months old, babies are spending an hour a day watching television, and by two, children are begging to play with smartphones and tablet devices. An accurate understanding of the role of media in children's lives is essential for promoting healthy development. The purpose of this study was to investigate how parents of preschoolaged children use mobile technology and to explore parents' perceptions about that technology use. This study involved a general quantitative methodology and design. The sample included 85 parents from three preschools in Turkey. Results revealed prevalent smartphone use by preschoolers, generally not for educational purposes but for games, causing some concern for parents. (C) 2014 The Authors. Published by Elsevier Ltd.
3rd Annual International Research-to-Practice Conference on Early Childhood Care and Education -- NOV 21-23, 2014 -- Russian Presidential Acad Natl Econ & Publ Adm, Moscow, RUSSIA
Keywords: mobile technology; preschool children and digital media; parents' perceptions; smartphones